The cholesterol metabolite 25-hydroxycholesterol suppresses porcine deltacoronavirus via lipophagy inhibition and mTORC1 modulation - Jia-lu Zhang; Xue-fei Wang; Jia-lin Li; Cong Duan; Jiu-feng Wang (Veterinary Research)
Abstract 25-Hydroxycholesterol (25HC) is a hydroxylated cholesterol with multiple antiviral activities, however, little is known about the mechanisms by which 25HC correlates antiviral ability with lipid droplet (LD) dynamic balance to ensure cholesterol homeostasis. In the present study, 25HC was applied to porcine deltacoronavirus (PDCoV)-infected LLC-PK1 (Lilly Laboratories Culture-Porcine Kidney 1) cells and piglets to explore its antiviral capacity and underlying mechanism. The results revealed that 25HC decreased free cholesterol (FC) levels but increased triglyceride (TG) levels in PDCoV-infected cells and piglets. The accumulation of LDs induced by oleic acid (OA) impedes PDCoV replication. In addition, 25HC administration increases LD accumulation and declines protein expression associated with lipophagy and lysosomes to facilitate LD accumulation. Moreover, 25HC inhibited TFEB (transcription factor-EB) expression, blocked its translocation into the nucleus and reversed Mechanistic Target of Rapamycin Complex 1 (mTORC1) activity, which in turn hindered lipophagy and PDCoV replication. Additionally, 25HC treatment ameliorated the clinical symptoms and intestinal injury of PDCoV-infected piglets. These findings reveal the beneficial effect of lipophagy on PDCoV infection and uncover the antiviral mechanism of 25HC, by which lipophagy and mTOR activity are tightly controlled by 25HC. Graphical Abstract